Platforms and public participation. Issue 6 (1st November 2016) - Butt, Danny; McQuire, Scott; Papastergiadis, Nikos
Abstract: The concept of the 'platform' has recently received extensive analysis in media studies and urban planning. This paper explores the platform's contemporary emergence as an expression of a new archival logic that questions the possibility of a democratic politics of participation. 'Public participation' in the platform invokes the individual in the form of a consumer with a profile rather than as a citizen of a state. This paper returns to Claudio Ciborra's 1996 work on the 'platform organization' to diagnose a 're-architecting' capability which we argue is integral to platform politics. Since this capacity for re-architecting is generally reserved from participants, we highlight the potential of 'de-participation' toward the emergence of counter-platforms.